A REVIEW ON “E BICYCLE LOCKING SYSTEM” (International Journal of Engineering Management Science, 2024)
Electronic locks have become more normal in structures and vehicles.The objective of the venture is to plan an electronic lock . The bike locking framework is produced for giving high level locking framework to the bikes and giving quick notice of robbery. Right now, bike burglary has expanded and frequently slips by everyone's notice. To increment the utilization of cycles the bike burglary ought to be diminished. This Bike locking framework works with the assistance of an electronic circuit having a secret key as the way in to the bike lock. A metal wire is associated so that the wire goes in the middle of between the tire spokes and into the framework. So assuming somebody attempts to take the cycle by breaking the lock it is detected by robbery identifying framework and caution is raised. Hearing the alarm the proprietor can get ready and attempt to stay away from burglary from occurring. The wire is utilized for the demo reason however serious areas of strength for a line can be utilized to lock tire. This wire is associated on to the framework through RCA connector This locking framework will diminish the robbery of cycles also, increment the utilization of cycles.
Keywords: Internet of Things, LED, DC Fan, Automation, sensors, web application, Data Analysis